Study Periodontal, Hygienic Indices of The Oral Cavity - Chaqqonov Faxriddin Xusanovich (Scientific Trends, 2024)
In recent decades, the question of the relationship between oral health and cardiovascular disease has been considered highly relevant. The effect of foci of chronic oral infection on the development of common diseases is recognized as important in all countries of the world (WHO, 2003). Thus, according to the World Health Organization, based on dental examinations of the population, periodontal disease occurs in 68-98%.